Cyber-OF: An Adaptive Cyber-Physical Objective Function for Smart Cities Applications - Ghazi Amor, Mohamed (2017)
Work in Progress Session, 28th Euromicro Conference on Real-Time Systems (ECRTS 2016). 5 to 8, Jul, 2016. Toulouse, France.